Correction: Prevention and management of type 2 diabetes mellitus in Uganda and South Africa: Findings from the SMART2D pragmatic implementation trial. - David Guwatudde; Peter Delobelle; Pilvikki Absetz; Josefien van Olmen; Roy William Mayega; Francis Xavier Kasujja; Jeroen De Man; Mariam Hassen; Elizabeth Ekirapa Kiracho; Juliet Kiguli; Thandi Puoane; Claes-Goran Ostenson; et al. (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0000425.].